Tumor-associated tissue eosinophilia in preinvasive and invasive squamous cell carcinoma of cervix - Sasturkar, Radhika C; BH, Ramesh; Nyamagoudar, Sunita; Jigjini, Sateesh S (Journal of Pathology of Nepal, 2022)
Background: Differentiating between preinvasive and invasive squamous neoplasms of the cervix can be a challenge in small, superficial fragments of cervical biopsy, particularly when inflammatory infiltrates obscure the epithelial stroma interface and due to tangential sectioning of the acanthotic squamous epithelium. This study evaluates whether thresholds of eosinophils in stroma serve as a morphological marker for the presence of tumor invasion in squamous neoplasms of the cervix. Material and methods: Sixty-five cases of invasive squamous cell carcinoma and preinvasive squamous neoplasia were evaluated. In each case, the number of eosinophils per HPF and per 10 HPF in the tissue adjacent to the neoplastic epithelium was counted. For statistical purposes, the elevated eosinophils were categorized as > 3 eosinophils/HPF, > 5 eosinophils/HPF, and >10/10 HPF. Results: Stromal eosinophils were present in 1/5 cases of LSIL, 3/8 HSIL cases, 15/16 cases of microinvasive squamous cell carcinoma, and 34/36 cases of invasive squamous cell carcinoma, signifying an increase in eosinophil count from a spectrum of preinvasive to invasive carcinoma. Greater than 5 eosinophils/HPF and >10 eosinophils/10 HPF had sensitivity, specificity, and positive predictive values of 55%, 100%, 100%, and 75%, 100%and 100%, respectively. The difference of >5eosinophils/HPF and >10eosinophils/10 HPF between SIL and SCC was statistically significant. Conclusions: Our study suggests that the presence of increased eosinophils in squamous neoplasia of the cervix can be associated with tumor invasion and should prompt a thorough evaluation when evidence of invasion is absent.